Effect of Using the iMPASIQ Application on Knowledge and Behavior of Mothers as an Effort to Prevent Stunting - Yhen Ari Bekti; Yuly Peristiowati (Budapest International Research and Critics University, 2022)
The research objective is to analyze effect of using the iMPASIQ application on knowledge and behavior of mothers as an effort to prevent stunting. This research is a quantitative research. This researcher uses a pre-experimental design using one group pre-test post-test. The sample in this study is 105 people who are taken by simple random sampling. To test the hypothesis, non-parametric statistical analysis was performed with the wilcoxon signed ranks test. The results of statistical calculations using the wilcoxon signed ranks test can be concluded that there is an effect of using the iMPASIQ application on knowledge and behavior of mothers as an effort to prevent stunting.